2020
DOI: 10.3389/fgene.2020.00276
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Association of Genetic Variants With Refraction, Axial Length, and Corneal Curvature: A Longitudinal Study of Chinese Schoolchildren

Abstract: Background: Myopia is a common eye disorder that is approaching epidemic proportions worldwide. A genome-wide association study identified AREG (rs12511037), GABRR1 (rs13215566), and PDE10A (rs12206610) as being associated with refractive error in Asian populations. The present study investigated the associations between these three genetic variants and the occurrence and development of myopia, spherical equivalent refraction (SER), axial length (AL), and corneal curvature (CC) in a cohort of southeastern Chin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 35 publications
1
5
0
Order By: Relevance
“…These results agreed with those in experimental myopia because the mRNA and protein expression of scleral AREG was increased with a prolonged covering time and decreased after the coverings were removed 13 . A genome‐wide association study found that the AREG SNP (rs12511037) was associated with increased AL, indicating that AREG is etiologically relevant for ocular traits 28 . Jonas et al found that the intraocular amount of EGF is higher in highly myopic eyes than in non‐highly myopic eyes, indicating a close association between the EGF family and myopia 29 .…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…These results agreed with those in experimental myopia because the mRNA and protein expression of scleral AREG was increased with a prolonged covering time and decreased after the coverings were removed 13 . A genome‐wide association study found that the AREG SNP (rs12511037) was associated with increased AL, indicating that AREG is etiologically relevant for ocular traits 28 . Jonas et al found that the intraocular amount of EGF is higher in highly myopic eyes than in non‐highly myopic eyes, indicating a close association between the EGF family and myopia 29 .…”
Section: Discussionsupporting
confidence: 84%
“…13 A genome-wide association study found that the AREG SNP (rs12511037) was associated with increased AL, indicating that AREG is etiologically relevant for ocular traits. 28 Jonas et al found that the intraocular amount of EGF is higher in highly myopic eyes than in non-highly myopic eyes, indicating a close association between the EGF family and myopia. 29 In conclusion, measuring AREG in tears could serve as an important surrogate marker to probe myopia mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Another study showed a 10.72 D shift toward myopia for every 1 unit of an increase in the AL/CRC ratio in Chinese schoolchildren aged 6–12 years ( He et al, 2015 ). Several genes were shown to be associated with AL and AL/CRC; however, previous studies did not report associations between TGFBR1 and AL or AL/CRC ( Cheng et al, 2013 ; Miyake et al, 2015 ; Li et al, 2020 ; Lin et al, 2020 ; Tang et al, 2020 ). Therefore, the present 3.5-year cohort study demonstrated that the TGFBR1 polymorphism was significantly associated with an increase in AL and AL/CRC.…”
Section: Discussionmentioning
confidence: 90%
“…Several studies identified an association between GABRR1 and myopia (Supplementary Table S6 and Figure 8). A genome-wide association study identified GABRR1 as one of the genes associated with refractive error in Asian populations (Fan et al, 2016;Lin et al, 2020). TPMPA ((1,2,5,6-tetrahydropyridin-4-yl)methylphosphinic acid)), a GABA-C antagonist has been shown to inhibit synaptic transmission in rat spinal cord (Rozzo et al, 1999), modulate sleep-waking behavior in rats (Arnaud et al, 2001), enhance memory in chicks (Gibbs and Johnston, 2005) and most importantly, inhibit myopia development in chicks and guinea pigs (Chebib et al, 2009;Cheng et al, 2014;Stone et al, 2003), indicating possible roles for GABA-C receptors in memory, circadian rhythms, and myopia (Cheng et al, 2011).…”
Section: Synapsementioning
confidence: 99%